Crystal structure of poly[chlorido-μ2-chlorido-(μ2-1-[(2-ethyl-4-methyl-1H-imidazol-1-yl)methyl]-1H-benzotriazole-κN:N’)cadmium(II)], C13H15CdN5Cl2 - Du Jun-Ya; Zhou Tan-peng; Yang Jing; Wang Xia (Zeitschrift für Kristallographie - New Crystal Structures)
C13H15CdN5Cl2, monoclinic, P21/c (no. 14), a = 11.5514(4) Å, b = 16.7843(5) Å, c = 8.9691(3) Å, β = 101.927(3)∘, Z = 4, V = 1701.41(10) Å3, Rgt(F) = 0.0379, wRref(F2) = 0.1020, T = 293(2) K.